Risk of falling in pediatric nursing - Jana Chromá (University of Ostrava, 2016)
Aim: The aim of this article is to describe, analyze and compare the assessment tools used to evaluate risk of falling in pediatric nursing. Design: Review - literature review. Methods: Electronic licensed and freely accessible databases (Bibliographia Medica Čechoslovaca, MEDLINE, Web of Science, PubMed a Scopus) were used to obtain data. Instruments for measuring risk of falling in languages other than Czech, Slovak or English, and scales unsuitable for measuring risk of falling in pediatric nursing were excluded from the analysis. Results: From analysis of the collected information, the most suitable tool for assessment of risk of falling in pediatric nursing seems to be the Humpty Dumpty measuring scale. Conclusion: At present there are many assessment tools that can be used to evaluate the risk of falling in pediatric nursing, but most are available in English. Czech pediatric nursing continues to lack measuring tools with verified psychometric properties.